Timber industries and licensing system in Malaysia - Hassan Zaki, Pakhriazad; Ismail, Mohd Hasmadi (Forestry Department Peninsular Malaysia, 2009)
This paper discusses the licensing system of Malaysia's sawmilling and plywood industries which has grown in tandem with the massive land development program begun in the 1960s. Since then, the industry has contributed a significant amount of government revenue, employment opportunities and foreign exchange. Progressive development of the sector has been underpinned by various governmental policies and regulations to nurture legal timber supplies for down-stream processing as well as developing secondary and tertiary processing industries. Policies provide various incentives to modernize the industries in order to upgrade processing efficiency, diversification into value-added and quality products and reduction of processing residues. This includes wider use of the under-utilized timber species as part of an effort to attain a rational balance between national processing capacity and resource availability. Various strategies have been targeted to enhance efficient utilization of all forms of forest products from legal sources. In addition, timber production and licensing are now closely monitored and regulated throughout the supply chain management.